Dokumentering av fastspänningar : En kvalitativ studie om konsten att dokumentera en tvångsåtgärd inom den psykiatriska slutenvården - Henriquez,Manuel; Asterhag,Frida (2015)
The aim of this study was to examine how documenting restraints is perceived by practitioners within closed psychiatric care. We used semi-structured interviews to interview five senior physicians working within inpatient care in Sweden. We asked them to describe their experience of documenting this procedure. We also asked them what attitudes they have towards the subject. A combination of the norm-model and organizational theory, more specifically organizations as cultures, provided us with the theoretical tools to analyze the doctors statements. The participants saw the end product of documenting, the documentation, as important towards the patient's legal rights. But most saw documenting as a barrier that took time away from the patient's physical care. Doctors prioritized the patients needs rather than documenting restraint procedures. Our conclusion is that the health care’s shared values of patient care makes doctors prioritize work with care needs rather than documentation at times when one must choose. Also policy makers should consider if the transparency requirements that come along with documentation are too high if these affect the professional's work to such an extent that they must decide between patient care and to meet these standards.
Keywords: lag; fastspänning; dokumentering; praxis; restraints; compulsory psychiatric care; documentation; law; practice